Investigating the Driving Forces of Energy Intensity Change in Malaysia 1991-2010: A Structural Decomposition Analysis - Abdullah, Azlina; Bekhet, Hussain Ali (International Journal of Energy Economics and Policy, 2019)
This research investigates the changes in Malaysia's energy intensity from 1991 to 2010 using structural decomposition analysis. Energy mix, sectoral energy efficiency, production structure, final demand structure, and final demand components factors are analysed. Results show that energy intensity has increased, and the responsible factors of this change were production structure, final demand structure, and sectoral energy efficiency. Further, this increase was offset by the negative effect of the change in final demand components owing to smaller positive net exports (due to a larger increase in imports compared with the increase in exports) plus with lower investment in 2010 compared with 1991. In addition, energy mix change also has contributed to energy intensity decline but at a minimal extent. The prominent effect of the production structure factor can be explained by the industrialisation occurring in the country. The economic plans, which, among others, promote several energy intensive industries, had dampened energy efficiency initiatives. Policy suggestions are proposed to reduce the energy intensity of Malaysia. Keywords: Energy Intensity, Energy Efficiency, Structural Decomposition Analysis, Input-output Model, Malaysia JEL Classifications: C67, O44, Q43 DOI: https://doi.org/10.32479/ijeep.7793